ANALYSIS OF “THE OLD MAN AND THE SEA” BY ERNEST HEMINGWAY - Oygul Tukhtaeva Erkin qizi (Journals Park Publishing, 2023)
The Old Man and the Sea is a rare work that embodies the concepts of trust and hope.
Keywords: apprentice “shogird”, symbol of a faithful, proud of his achievement, cann’t be defeated, suspicions.